EDUKASI KESEHATAN MATA DI ERA DIGITAL: PENGABDIAN KEPADA MASYARAKAT DI SDN PONDOK RANGGON 4 JAKARTA TIMUR - Sahel Sahel; Atti Kartikawati; Suci Haryanti; Shinta Amelia Astuti; Fitri Yati (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The prevalence of refractive errors in children has increased significantly in the digital era, especially since the COVID-19 pandemic. Excessive use of gadgets without proper management can cause digital eye strain and increased risk of myopia. This community service activity aims to conduct refraction examinations, provide eye health education, and provide free glasses to students and teachers at SDN Pondok Ranggon 4 East Jakarta. The methods used include eye health screening, refraction examination, eye health education in the digital era, and distribution of glasses. The results showed that of 446 respondents examined, 164 people (36.77%) required glasses correction. The highest prevalence of refractive errors was found in teachers and staff (100%), followed by grade 5 (52.12%), grade 3 (36.92%), and grade 4 (18.46%). This activity made a positive contribution to increasing awareness and knowledge of the school community about the importance of eye health in the digital era and providing adequate access to vision correction.